Entomopathogenic fungi in Southeast Asia and Africa and their possible adoption in biological control - Julius Rajula (2020)
© 2020 Elsevier Inc. Entomopathogenic fungi (EPF) are fungal species that are pathogenic to insects. These fungal pathogens play an important part in controlling insect population making them the first insect pest control factors. Currently, more than 750 species of fungi from around 90 genera are known to be pathogenic to insects classified in several phyla namely: Chytridiomycota, Ascomycota, Basidiomycota, and the subphylum Entomophthoromycotina. The EPFs contain a plethora of advantages such as being environmentally safe, can be mass-produced, and having the ability to infect the insect hosts through the cuticle instead of waiting for ingestion in order to cause infection. Moreover, it has been established that they can target almost every stage of insect cycle, making them a unique component in the integrated pest management approaches. This review is aimed at finding out how these microorganisms have been studied and adopted for biological control in Southeast Asia and Africa and their possible utilization in integrated pest management. From the published literature, it is apparent that EPFs are ubiquitous both in Southeast Asia and Africa. These fungi have been isolated in various habitats and identified, but unfortunately, there are not many formulations produced that can be commercially utilized in agriculture and forestry. Therefore, concerted efforts are needed so that we can adopt the usage of these important fungi in controlling insect pests and also implement them in Integrated Pest Management (IPM).